Increasing the competency of midwives through credential management training at RSU Islam Harapan Anda, Tegal City - Fitriani Nur Damayanti; Umi Khasanah; Puji Nur Fatimah; Yoni Meilinda Putri Stiawan (Universitas Muhammadiyah Magelang, 2024)
In the era of globalization, hospitals are required to ensure high performance among midwives in delivering services to the community, particularly to patients. However, a lack of knowledge among midwives regarding midwifery credential management has been noted to impact their performance and the quality of midwifery services within hospitals. The objective of midwifery credential training activities is to enhance the quality of midwifery services at RSU Islam Harapan Anda in Tegal City. This community service initiative engaged 30 midwives from RSU Islam Harapan Anda. The training employed two methods: lectures and practical sessions. Results from the training indicated significant improvements in knowledge levels among midwives (p < 0.05). Consequently, training on credential management through lectures and practical sessions can enhance midwives' understanding of credential management and reinforce their knowledge of competencies and authorities, thus enabling them to provide better midwifery services and improve overall service quality within hospitals.